Selection matrix for Brazilian bee species to risk assessment of pesticides - Viana-Silva, Flavia; Pires, Carmen; Torezani, Karoline; Borges, Leandro; Cham, Karina; Dias, Cristiane; Teixeira, Ivan; Tonelli, Carlos; Belchior, Ceres; Marcondes, Cayssa; Nocelli, Roberta; Malaspina, Osmar [UNESP]; et al. (Julius Kuhn-inst, 2018)
Many countries are using honeybee (Apis mellifera) as a surrogate to evaluate the risk of pesticides to all bee species. However, there is uncertainty regarding the extent honey bees can be used as surrogates for non-Apis species in pesticides risk assessment. A selection matrix for Brazilian bee species was built to support the selection process. To be considered as a candidate representative species in the Brazilian agricultural scenario a bee should have a wide geographic distribution, and be recorded in at least 4 agricultural crops. The selection matrix provides a foundation to elect meliponines (stingless bees) as a priority group. Therefore, in the near future lbama intends to assess the need for changes in the risk assessment procedure for bees, eventually including a stingless bee as a representative species.
Keywords: selection matrix; non-Apis bees; risk assessment; pesticides